Suicidal Behavior and Psychosocial Outcome in Borderline Personality Disorder at 8-Year Follow-Up - Soloff, Paul H.; Chiappetta, Laurel (Journal of personality disorders, 2017)
We sought predictors of both suicidal behavior and psychosocial outcome in subjects with BPD followed for 8 years and asked if there was a relationship between these outcomes. One hundred twenty-three BPD subjects, recruited from inpatient (35.8%), outpatient (30.9%) and community (33.3%) sources, were assessed annually for known risk factors for suicidal behavior. Interval attempts were reported by 25 subjects (20.2%). Increased risk of suicide attempt was associated with negative affectivity, aggression, inpatient recruitment, hospitalizations, minority race, and frequent changes in employment. Decreased risk was associated with increased education. Poor psychosocial outcome was predicted by impulsivity, negative affectivity, and antisocial traits at baseline, and by comorbid MDD at 8-year follow-up. There was no significant relationship between poor psychosocial outcome at 8-year follow-up and risk of suicidal behavior. Predictors of suicidality include modifiable risk factors. Rehabilitation models are needed to address educational and vocational deficits associated with suicidality, especially among minorities.